2021
DOI: 10.18316/sdh.v9i1.6224
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre as variáveis individuais e ambientais do contexto escolar com a aptidão cardiorrespiratória de adolescentes

Abstract: Objetivo: O objetivo do presente estudo foi identificar as associações das variáveis individuais e ambientais do contexto escolar com a aptidão cardiorrespiratória de adolescentes. Métodos: Estudo do tipo associativo, com abordagem quantitativa e corte transversal. Foi selecionada uma amostra de escolares do ensino médio da zona sul de Porto Alegre/RS. Foi avaliada a aptidão cardiorrespiratória, um conjunto de variáveis sobre o comportamento ativo e práticas esportivas (variáveis individuais) e a quantidade e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Evidently, the results of this study diverge from this statement that physical education classes are used to develop physical fitness. However, they may find support in the study by (Melo et al, 2021), who identified free-form classes that were completely unconcerned with physical fitness. Nevertheless, there are several elements that may interfere with the intensity and volume that students are subjected to in physical education classes, such as the existence and amount of sports equipment, among other things.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Evidently, the results of this study diverge from this statement that physical education classes are used to develop physical fitness. However, they may find support in the study by (Melo et al, 2021), who identified free-form classes that were completely unconcerned with physical fitness. Nevertheless, there are several elements that may interfere with the intensity and volume that students are subjected to in physical education classes, such as the existence and amount of sports equipment, among other things.…”
Section: Discussionmentioning
confidence: 97%
“…Another interesting point concerns the overloadintensityapplied in physical education classes in relation to low cardiorespiratory activity. This was associated with the objectives for physical education in their respective school units because the activities proposed by teachers had no concern for intensity, which decreases the possibility of overload and morphophysiological adaptation as a consequence (Melo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%